The End of the Story? Narrative Openness in Life and Death - Randall, William (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2019)
In this 2019 John McKendy Memorial Lecture,1 Dr. William Randall discussed how few topics intrigue us more than death. Yet few topics are more taboo—not unlike aging, with which, in many people’s minds, it can seem synonymous. But just as a narrative perspective on aging enables us to envision its more positive potentials in terms of meaning, wisdom, and spirituality, so a narrative perspective can shed a more redemptive light on death, presumably the final event in the story of our lives. Drawing on insights from psychology, gerontology, cosmology, theology, and literary theory, Dr. Randall used the concept of narrative openness to entertain alternative and ultimately enticing ways of storying the so-called end of life.